(X) = 6x ^ 5-5x ^ 4 + 4x ^ 3-3x ^ 2-2x + x + 7 ו- m (x) = x ^ 2-1, איך מוצאים את המנה h (x) ו- מ '(x)?

(X) = 6x ^ 5-5x ^ 4 + 4x ^ 3-3x ^ 2-2x + x + 7 ו- m (x) = x ^ 2-1, איך מוצאים את המנה h (x) ו- מ '(x)?
Anonim

תשובה:

# 6x ^ 5 + 5x ^ 4-3x ^ 3 + 2x ^ 2 + x-7 #

הסבר:

#h (x) = 6x ^ 5-5x ^ 4 + 4x ^ 3-3x ^ 2-2x + x + 7 #

#m (x) = x ^ 2-1 #

לפיכך, # x + 5 + x + = 4x ^ 3-3x ^ 2-2x + x + 7) (x ^ 2-1) # #

=# - (6x ^ 5-5x ^ 4 + 3x ^ 3-2x ^ 2-x + 1) # #

=# -6x ^ 5 + 5x ^ 4-3x ^ 3 + 2x ^ 2 + x + 1 #

לפשט # (- 2x + x) # ו # (- 3x ^ 2 ו- x ^ 2) #